CHANGES IN PHYSICOCHEMICAL PROPERTIES OF USED PALM OIL (JELANTAH) ON CHICKEN FRYING - Aminullah, Aminullah (JURNAL PERTANIAN, 2018)
Cooking oil was one of the basic needs which consumed by the whole of Indonesian society. The high price of palm cooking oil and the lack of knowledge caused the repeated using of palm cooking oil which is harmful to health. The objective was to determine the physicochemical changes of used palm oil (Jelantah) on chicken frying. This research was using purposive sampling method. The experimental design used completely randomized design with one factor of frying frequency which were 0, 3, 7 and 10 times. Statistical analysis showed that the physicochemical tests (color analysis, peroxide value, acid value and moisture content) in each test was significant or significantly different, from the linear regression predicted that the frying frequencies which were used in fried chicken vendors were 16-54 times. In addition, it can be seen the characteristic qualities of used palm oil on chicken frying namely: color analysis L from 39.40% to 46.49%, a from 5.80% to 9.26%, b from 16,57% to 22.82%; peroxide value from 1.599 meq/kg to5.623 meq/kg; acid value from 0.076% to 0.153%; and water content from 0.021% to 0.267%. The physicochemical tests of used palm oil sample from fried chicken vendors namely: color analysis at L of 27.11%, a of 9.63%, b of 18.02%; peroxide value of 10.07 meq / Kg; acid value 0.434%; and water content of 0.166%.